2011
DOI: 10.1039/c1mb05193h
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane proteome and its regulation networks in response to glucose concentration changes in Escherichia coli

Abstract: Escherichia coli growth is a complicated process involved in many factors including the utilization of glucose. It has been reported that E. coli cell growth rate is closely related with glucose concentrations in the cell culture medium. However, the protein regulation networks in response to glucose concentration changes are largely unknown. In the present study, a sub-proteomic methodology has been utilized to characterize alterations of E. coli OM proteins in response to 0.02, 0.2 and 2% concentrations of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…It was also observed that the growth rate of the TMT strain in M9 medium was 1.65 times lower when compared to the rate observed in PYG medium cultured TMT strain. Previous reports have observed that the porins OmpF and OmpC are differentially regulated by glucose concentrations because the two porins constitute the main glucose entry channels into the periplasm when the carbon source is present at a higher concentration of 0.2 mM (0.036 g/l) [38]. Cellular growth rate has been correlated to the uptake of glucose via OmpF and OmpC.…”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that the growth rate of the TMT strain in M9 medium was 1.65 times lower when compared to the rate observed in PYG medium cultured TMT strain. Previous reports have observed that the porins OmpF and OmpC are differentially regulated by glucose concentrations because the two porins constitute the main glucose entry channels into the periplasm when the carbon source is present at a higher concentration of 0.2 mM (0.036 g/l) [38]. Cellular growth rate has been correlated to the uptake of glucose via OmpF and OmpC.…”
Section: Resultsmentioning
confidence: 99%
“…Various regulatory cascades can be launched in response to changing environmental conditions. Among possible mechanisms involved in decreasing OM permeability due to OmpC-directed OM porin balance, we can mention the increased expression of bolA morphogene responsible for adaptive stress response in Enterobacteriaceae (Freire et al, 2006), and the TolC, LamB, and Dps proteins which can significantly influence OM protein network (Yang et al, 2011). Handling of the OM protein balance according to environmental factors may also be conditioned by the two-component regulatory system OmpR-EnvZ (Chhabra et al, 2012; Shimada et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors proved that mutations within histidine kinase CpxA showed the possible fixation of OmpC-directed OM polarization. It can be assumed that factors disturbing the physiological regulatory cascade may be associated with consistent OM protein balance polarization toward OmpC with restrictive channel or abnormal expression of both major porins (Malickbasha et al, 2010; Yang et al, 2011; Tängdén et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the correlation between the protein regulation, amino acid composition and codon usage pattern may thus help us to better understand the cell regulatory mechanisms and in many cases how protein regulation is involved in the (often poorly understood) protein networks [21]. However, an efficient bioinformatic method to systematically explore such relationships in the context of high-throughput proteomics has not yet been developed.…”
Section: Introductionmentioning
confidence: 99%